Penerjemahan Rambu Lalu Lintas Bilingual di Bali: Antara Makna dan Konteks - I Ketut Indra Prayogi; Manipuspika, Yana Shanti (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
This study aims to analyze the discrepancy between meaning and context in the translation of bilingual (Indonesian-English) traffic signs in Bali. This phenomenon is interesting to study, considering that Bali, as an international tourist destination, demands that foreign tourists understand public information. This study uses a qualitative descriptive approach with a case study method. Data were collected through documentation and observation of signs found in tourism areas. The analysis was conducted based on the translation principles according to Vinay and Darbelnet's theory. The results show that there are discrepancies in meaning due to the application of literal translation techniques and a lack of understanding of the cultural and functional context of the signs. In addition, it was found that some translations contain ambiguities, grammatical errors, and the translators did not consider the target audience. These findings indicate a low competence in selecting appropriate translation techniques, which impacts the quality of public sign translations in Bali as a tourism area. Therefore, the study recommends technical translation training, the development of standard sign translation guidelines, intersectoral collaboration, and further research using other theoretical approaches. With these steps, it is hoped that the translation of bilingual traffic signs in Bali can be more accurate, communicative, and effective in conveying messages to local people and tourists.